2017
DOI: 10.3390/ijerph14060657
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Risk Factors for Oral Clefts in Northern Africans, Southeast Asians, and Central Americans

Abstract: While several studies have investigated maternal exposures as risk factors for oral clefts, few have examined paternal factors. We conducted an international multi-centered case–control study to better understand paternal risk exposures for oral clefts (cases = 392 and controls = 234). Participants were recruited from local hospitals and oral cleft repair surgical missions in Vietnam, the Philippines, Honduras, and Morocco. Questionnaires were administered to fathers and mothers separately to elicit risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…We found when family history adjusted for consanguinity remained significantly associated with the presence of CM in children the aOR 2.23 and the (P 0.007). In accordance with the studies were conducted in Northern Africans, Southeast Asians and Central Americans [19]. Among the maternal characteristics, prematurity (< 37 completed weeks) was a significant risk factor which is similar to studies done in United State and England [20,21].…”
Section: Discussionsupporting
confidence: 85%
“…We found when family history adjusted for consanguinity remained significantly associated with the presence of CM in children the aOR 2.23 and the (P 0.007). In accordance with the studies were conducted in Northern Africans, Southeast Asians and Central Americans [19]. Among the maternal characteristics, prematurity (< 37 completed weeks) was a significant risk factor which is similar to studies done in United State and England [20,21].…”
Section: Discussionsupporting
confidence: 85%
“…conducted an international study on paternal factors. They concluded that a father’s personal or family history of CLP was linked to a noticeably higher risk [ 56 ]. In the study of Noorollahian et al a family history of this disease was present in about one-third of the cases [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Water pollution also proved a significant risk factor. Figueiredo et al reported a higher incidence of OFCs in the offspring of mothers who drew water from a well than in controls who took filtered water or water drawn from public waterworks [ 56 ]. Nevertheless, water disinfection by-products (DBPs), which are formed by the interaction of chemical disinfectants and organic material in the water, are a hazard for OFCs’ occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Our data further confirmed increasing paternal age as a risk factor for cleft palate only and found no association between maternal age and risk of cleft palate only after adjustment. 37,[54][55][56][57][58][59] Compared with receiving prenatal care in the first trimester, lack of prenatal care or beginning prenatal care in the second or third trimester increased the risk of cleft lip with or without cleft palate. This may be mediated by the prevention of vitamin and mineral deficiencies and identification of harmful exposures that may disrupt embryonic orofacial development.…”
Section: Other Maternal Paternal and Infant Risk Factors For Cleftsmentioning
confidence: 99%